In-vitro Assessment of Antifungal Activity of Aloe vera Leaf Powder Extracts Against Banana Pseudostem Rot Fungi, Marasmiellus spp - Nivethika, A.; Mikunthan, G. (My University, 2016)
Being an important medicinal plant, Aloe vera is important in industrial perspective as well as traditional usage. The antifungal activity of A. vera leaf powder extracts were assessed against banana pseudostem rot fungi, Marasmiellus spp. Leaf powder with acetone and ethanol extracts of 20, 200, 400, 1000 and 2000 µL were administered to assess the inhibition of colony growth of Marasmiellus spp. The experiment was conducted in a CSompletely Randomized Design. In A. vera acetone extract, first day after inoculation, inhibition percentage of the Marasmiellus spp was higher (74.53 %) in 2000 µL and the lowest percentage (23.53 %) of inhibition was obtained in 20 µL of A. vera acetone extract. The similar highest and lowest percentage of inhibition were observed in second, third and fourth day after inoculation. In A. vera ethanol extract, complete (100 %) inhibition was observed in 1000 µL and 2000 µL extracts. The lowest inhibition (2.26 %) was recorded in 20 µL of A. vera ethanol extract. Among the 1000 µl and 2000 µL leaf extracts, ethanol extract had the highest inhibition percentage compared to A. vera acetone extract. These findings are useful to prepare the extracts of A. vera leaf powder for the management of Marasmiellus spp.
Keywords: Aloe vera; Antifungal activity; Banana pseudostem rot; Colony inhibition; Marasmiellus spp